SOLUBILITY AND DISSOLUTION RATE ENHANCEMENT OF EZETIMIBE BY SOLID DISPERSION AND PELLETIZATION TECHNIQUES - KUNAM, VISWANADH; SURYADEVARA, VIDYADHARA; RAO GARIKAPATI, DEVALA; MANDAVA, VENKATA BASAVESWARA RAO; SUNKARA, SIVA PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In the present investigation, an attempt was made to improve the surface characters and solubility of the drug by solid dispersion and coating it on the non-pareil sugar beads as pellets. Methods: Ezetimibe solid dispersions were prepared by solvent evaporation technique using Kollidon VA64 as binder and solubility enhancer. Crospovidone as disintegrant and ethanol was used as solvent. Ezetimibe pellets were prepared by dissolving ezetimibe, kollidonVA64, and crospovidone in ethanol in different ratios and coated on non-pareil sugar beads as a drug layer by pan coating technique. Results: All the formulations were further evaluated for physicochemical parameters such as particle size, friability, angle of repose, and drug content. In vitro dissolution studies were carried out in 1% sodium lauryl sulfate using USP apparatus II. Conclusion: It was observed that the dissolution rate of the solid dispersion formulation ESD5 showed better dissolution rate to the extent of 1.05 folds and 1.824 folds when compared to a marketed formulation and pure drug, respectively. Similarly, formulation EPL5 containing 1:5 ratio of ezetimibe to Kollidon VA64 showed improved dissolution rate to the extent of 1.091 folds and 1.986 folds when compared to the marketed formulation and pure drug, respectively. Majority of the formulations displayed first-order release kinetics and were found to be linear with R2 values in the range of 0.874–0.993. Fourier transform infrared analysis revealed that there was no major interaction between the drug and excipients used in the design of formulation. Scanning electron microscopy analysis was performed for solid dispersions, pellet formulations, and its polymers to determine the surface characteristics.